STRATEGI PENINGKATAN NILAI TAMBAH DAN PEMASARAN PRODUK HASIL OLAHAN IKAN AIR TAWAR DI DESA BUNKATE KECAMATAN JONGGAT, KABUPATEN LOMBOK TENGAH - Miftahul Khair; Ramadhani, Aulia; Soleha, Hilalia; Siambaton, Rini Ramdani; Faqih, Farid; Kiamuddin, Moh.; Haryani, Dewina; Nurasmi, Intan; Hartiwi, Hartiwi; Redi, Muhammad; Agusdin, Agusdin (Universitas Mataram, 2025)
Bunkate Village, Jonggat District, Central Lombok Regency, has fisheries potential, especially freshwater fish farming, but this potential has not been optimally managed. KKN-PMD students from Mataram University initiated technical guidance and processing and marketing activities for freshwater fish farming products. This activity includes training in making fish sticks as one of the product form diversifications and education on effective food product marketing strategies. The program implementation method includes observation, interviews with fish farmers, recipe formulation, and implementation of technical guidance attended by the surrounding community, especially PKK mothers. The results of the activity showed that participants were enthusiastic in participating in the training and gained new skills in processing tilapia into products with higher selling value in the form of fish sticks and marketing strategies for fishery products, which are expected to increase the income and welfare of the village community. Through this activity, it is hoped that the Bunkate Village community will be able to develop fisheries-based businesses independently and sustainably, thereby increasing the welfare of the village community, especially freshwater fish farmers.